Solid Waste Management Practices of Printing Firms in Uyo, Akwa Ibom State - Ubong s., Akpan; Ekenedo, Golda (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
The study aimed at determining the solid waste management practices of printing firms in Akwa Ibom State. The study was a descriptive survey. A multi-stage sampling procedure was employed in the selection of 560 workers in the printing industry while a self-structured and validated questionnaire with a reliability index of 0.91 was used as instrument for collecting data from the respondents. Descriptive statistics of percentage was used for analysis of the data collected. The findings of the study showed that the printing firms in Uyo, Akwa Ibom State had good waste collection practices in that 98.4% had waste collection bin and 56. % sorted their waste but practiced environmentally unhealthy methods of waste disposal (74.3% of workers disposed of waste by throwing them away and 37.6% threw waste into rivers and streams). Based on the findings, it was recommended among others that government should build recycling plants and encourage public support towards effective utilization through attractive policies